2019
DOI: 10.1002/14651858.cd004421.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Taxanes for adjuvant treatment of early breast cancer

Abstract: Trusted evidence. Informed decisions. Better health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 93 publications
1
51
0
6
Order By: Relevance
“…Wang, Li, Zhao, and Zhang (2018) demonstrated that oestrogen levels influence TNF‐α production in the DRG and are correlated with the neuroinflammation caused by paclitaxel, as both mechanical and thermal hypersensitivities are attenuated by bilateral ovariectomy in rats (Wang et al, 2018). This is an important observation as taxanes are used in the chemotherapy schemes for the treatment of breast cancer in women at pre‐ or post‐menopausal phases (Willson et al, 2019). The influence of sexual hormones in taxane‐induced peripheral neuropathy has been supported by another study, which showed that the intrathecal administration of the pro‐resolution mediator resolvin D5 reduces paclitaxel‐induced mechanical allodynia in male but not female mice (Luo, Gu, Tao, Serhan, & Ji, 2019).…”
Section: Taxane‐induced Peripheral Neuropathymentioning
confidence: 99%
“…Wang, Li, Zhao, and Zhang (2018) demonstrated that oestrogen levels influence TNF‐α production in the DRG and are correlated with the neuroinflammation caused by paclitaxel, as both mechanical and thermal hypersensitivities are attenuated by bilateral ovariectomy in rats (Wang et al, 2018). This is an important observation as taxanes are used in the chemotherapy schemes for the treatment of breast cancer in women at pre‐ or post‐menopausal phases (Willson et al, 2019). The influence of sexual hormones in taxane‐induced peripheral neuropathy has been supported by another study, which showed that the intrathecal administration of the pro‐resolution mediator resolvin D5 reduces paclitaxel‐induced mechanical allodynia in male but not female mice (Luo, Gu, Tao, Serhan, & Ji, 2019).…”
Section: Taxane‐induced Peripheral Neuropathymentioning
confidence: 99%
“…CIPN is a common side effect of many chemotherapy regimens with an aggregate prevalence of 68.1% [21] Severe CIPN is especially dramatic among patients receiving taxanes for adjuvant treatment of early breast cancer [22].…”
Section: Discussionmentioning
confidence: 99%
“…Two exploratory analyses performed in the E2197 study [79] and the CALGB trials [80] confirmed that taxanes were more effective in HR-negative tumors compared with HR-positive ones. However, an updated Cochrane systematic review including 29 adjuvant trials reported increased survival by adding taxanes to standard anthracycline-based chemotherapy with no different treatment effect by subgroups for HR status [81].…”
Section: Taxanesmentioning
confidence: 99%